Molecular mechanism of circRNAs in drug resistance in renal cell carcinoma - Shuang Qin; Yuting Wang; Peijun Wang; Qi Lv (Cancer Cell International, 2022)
Abstract Renal cell carcinoma (RCC) is one of the most common malignant tumors with a poor response to radiotherapy and chemotherapy. The advent of molecular targeted drugs has initiated great breakthroughs in the treatment of RCC. However, drug resistance to targeted drugs has become an urgent problem. Various studies across the decades have confirmed the involvement of circular RNAs (circRNAs) in multiple pathophysiological processes and its abnormal expression in many malignant tumors. This review speculated that circRNAs can provide a new solution to drug resistance in RCC and perhaps be used as essential markers for the early diagnosis and prognosis of RCC. Through the analysis and discussion of relevant recent research, this review explored the relationship of circRNAs to and their regulatory mechanisms in drug resistance in RCC. The results indicate an association between the expression of circRNAs and the development of RCC, as well as the involvement of circRNAs in drug resistance in RCC.